1982
DOI: 10.1128/aac.22.4.696
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RNA Viruses In Vitro and in Rift Valley Fever-Infected Mice by Didemnins A and B

Abstract: were dissolved in ethanol, reconstituted with Hanks balanced salt solution, and buffered to pH 7.2 with 10 mM HEPES (N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid) plus 2% (vol/vol) heat-inactivated fetal bovine serum (4% ethanol, final concentration). Drug solutions (0.3 ml) of appropriate concentration (0 to 2.5 ,ig/ml for didemnin A and 0 to 0.5 ,ug/ml for didemnin B) were added to 24-well tissue culture trays (Falcon). Virus (0.1 ml, 50 to 200 PFU) or medium (for tissue culture toxicity controls) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 3 publications
1
26
0
Order By: Relevance
“…Both the A and B congeners showed comparable in vitro inhibitory effects against the viruses causing RVF, Venezuelan equine encephalomyelitis, and yellow fever. The inhibition was observed at concentrations similar to those initially reported by Rinehart et al, with didemnin B consistently showing a roughly tenfold potency enhancement relative to didemnin A. Additionally, Canonico et al 27 reported the ®rst results showing in vivo ef®cacy of didemnins. At a dose of 0.25 mg/kg/day of didemnin B, mice infected with RVF virus had a 90% survival rate, although some unspeci®ed fatal drug-related deaths were observed.…”
Section: Antiviral Activitysupporting
confidence: 66%
See 1 more Smart Citation
“…Both the A and B congeners showed comparable in vitro inhibitory effects against the viruses causing RVF, Venezuelan equine encephalomyelitis, and yellow fever. The inhibition was observed at concentrations similar to those initially reported by Rinehart et al, with didemnin B consistently showing a roughly tenfold potency enhancement relative to didemnin A. Additionally, Canonico et al 27 reported the ®rst results showing in vivo ef®cacy of didemnins. At a dose of 0.25 mg/kg/day of didemnin B, mice infected with RVF virus had a 90% survival rate, although some unspeci®ed fatal drug-related deaths were observed.…”
Section: Antiviral Activitysupporting
confidence: 66%
“…Canonico et al 27 reported that didemnins A and B were able to protect mice against lethal doses of the Rift Valley fever (RVF) virus. Reportedly, there existed no effective therapy for this virulent human pathogen.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…In addition to their antitumor activity, they exhibited in vitro and in vivo antiviral properties. Didemnin B significantly reduced the yields of DNA and RNA viruses by 104-105 at 0.5 IJ.g/ml, and in in vivo tests protected over 70% of a population of mice from lethal vaginal doses of herpes simplex type 2 virus (intravaginal application three times per day) (Rinehart et al, 1983), and a lethal subcutaneous challenge of Rift Valley fever virus with a 90% survival rate at 0.25 mg/kg (Canonico et al, 1982).…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…Iodine (30 mg, 0.24 mmol) in CH 2 Cl 2 (1.2 ml) was added to didemnin B (33 mg, 0.03 mmol) and dry silver trifluoroacetate (26.4 mg, 0.12 mmol) in dry methylene chloride (1.2 ml) [7]; stirred overnight; diluted with CH 2 Cl 2 ; the silver iodide was filtered; the filtrate was washed with 5% aqueous Na 2 Iododidemnin B (20 mg, 0.018 mmol) in dimethylformamide (0.6 ml) was reacted with 5% Pd/C (20 mg) and PtO 2 (7.0 mg) in a flask connected to a tritium source for 3 days; the mixture was diluted with ethanol (3 ml); filtered; and solvent removed via vacuum. The sample was purified on an ODS-HPLC with methanol/ H 2 O (83/17).…”
Section: Test Agentmentioning
confidence: 99%